Crystallinity effect on electron-induced molecular structure transformations in additive-free PLA. (16th January 2023) - Zhang, Yinglan; Müller, Michael Thomas; Boldt, Regine; Stommel, Markus
Abstract: Additive-free biodegradable polylactides (PLAs) with different crystallinities from 0 to 13.3% (according to x-ray diffraction, XRD) were used as starting materials modified by the electron beam (EB) with several irradiation doses at 25 °C (below glass transition temperature, g ) and 80 °C (>Tg ) in nitrogen. The crystallinity effects on radical decay and molecular structure transformation were investigated. After irradiation, the main stable radical remained in PLA is –O–C*(CH3 )–CO–. During irradiation, radical reactions were inhibited by high crystallinity. Large amounts of EB-induced crosslinking and long-chain branching (LCB) were introduced by performing irradiation at 80 °C. An increasing crystallinity has been found that restrained crosslinking and LCB due to the poor chain mobility in the crystalline areas. An increase of crystallinity from 0 to 13.3% obviously decreased the saturated crosslink content from 65% to 43% and restrained LCB formation. This study also verified that strict moisture control combined with applying an irradiation temperature above Tg can be a universal method to introduce large amounts of crosslinking and LCB in different grades of additive-free PLA. Graphical abstract: Image 1 Highlights: Radical reactions initiated by electron beam treatment are inhibited by high crystallinity, due to the poor chain mobility in the crystalline regions Generation of large amounts of cross-links and long-chain branching (LCB) in additive-free polylactide (PLA) by electron beam irradiation. Limited cross-linking and LCB by increasing degree of crystallinity Verification of strict moisture control combined with applying an irradiation temperature above glass transition temperature that is a universal method to introduce large amounts of cross-links and LCB in different grades of additive-free PLA.